A Skill Enhancement and Artistic Development Approach: The Variation Steps Training Program for Student Dancers in Iligan City - Estudillo, Clinton Butch; San Diego, Chiedel Joan; Maghanoy, Vanessa; Santillana, Leo; Malayao, Sotero (Asia Research Network Journal of Education, 2025)
This study aimed to conceptualize, design, and implement a comprehensive Variation Steps-focused dance training program to enhance skill proficiency, artistic expression, and stage readiness among student dancers in Iligan City. Guided by the Input-Process-Output (IPO) model, the study assessed the effectiveness of a progressive training framework tailored to the needs of youth engaged in competitive dance. Using both quantitative and qualitative approaches including surveys, interviews, and expert-based performance assessments the study found significant improvements in rhythm, coordination, footwork precision, and stage presence. The program’s success offers a replicable model for community-based dance pedagogy and contributes to the scholarly discourse on skill enhancement through structured dance education.